FAKTOR-FAKTOR YANG MEMPENGARUHI MENUNDA MENIKAH PADA DEWASA - Zulfitri, Wulan; Rahayu Z, Sri Putri (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2024)
Delaying marriage is a simple and straightforward method to strengthen the process of forming a relationship with a type of person, indicating that there is no desire to understand life's challenges. This study uses literature review techniques, searching journals and articles written in both Indonesian and English to identify the factors that influence young people's perception of their future. Several factors that negatively impact people include the desire to focus on career and work, the desire to balance personal life with work, economic downturns, the trauma of losing a loved one, and the inability to make sound financial decisions.